Profitability Analysis of Transportation and Logistics Sector Companies listed on the Indonesia Stock Exchange - Choirunisa, Fitri; Takarini, Nurjanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Profitability is one of the important measures of a company's success and is very important in financial terms. The purpose of this study is to determine whether the profitability of companies listed on the Indonesia Stock Exchange in the transportation and logistics industry is influenced by liquidity, leverage, activity, and company size. This study conducted multiple linear analysis. The study involved 30 businesses, with 28 samples that met the criteria. The main data from www.idx.co.id was used for this study. which was then processed by the researcher.The results of multiple linear analysis in this study indicate that (1) Liquidity, Leverage, Activity, Company Size have a positive effect on profitability simultaneously. (2) Liquidity and activity have a positive effect on profitability partially (3) Leverage and company size have a negative effect on profitability partially.